PENGARUH CAPITAL, ASSET, EARNING DAN LIQUIDITY TERHADAP PERUBAHAN HARGA SAHAM BANK - Lestari, Saptorini Dyah; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of capital, assets, earning, and liquidity to the changes of stock price on the banking companies which are listed in Indonesia Stock Exchange. The samples have been selected by using purposive sampling technique to the 31 banking companies which have been published their financial statement in 2011-2013 periods, therefore 93 financial statements which meet the sample criteria have been obtained. The analysis technique has been done by using Multiple Regression Analysis and the independent variables i.e.: Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return Of Asset (ROA), Return Of Equity (ROE), Loan to Deposit Ratio (LDR) and the dependent variable i.e.: Stock Price Change (PHS). The result of the research has found that the Capital Adequacy Ratio (CAR), Return Of Asset (ROA), Return Of Equity (ROE) variables have significant influence to the changes of stock price, meanwhile the Non-performing Loan (NPL), and the Loan to Deposit Ratio (LDR) does not have any significant influence to the stock price, and the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return Of Asset (ROA), Return Of Equity (ROE), and Loan to Deposit Ratio (LDR) variables have significant influence to the changes of stock price.Keywords: CAR, NPL, ROA, ROE, LDR and PHS